The Effect of Electronic Medical Records on Service Quality and Patient Satisfaction: A Literature Review - Dede Setyadi; Mardiati Nadjib (Publikasi Indonesia, 2023)
Background: Electronic medical records (EMR) are important to implement because they reduce doctors' workload, costs and errors. With Electronic Medical Records, Doctors and health workers also benefit from easy access to patient information which ultimately helps improve patient safety and clinical decision-making such as diagnoses, allergic reactions, and drug duplication. Electronic Medical Record (EMR) benefits patients because of efficiency in the health care process. Therefore, the purpose of this study was to review the literature on the implementation of EMR on service quality and patient satisfaction. Methods: A systematic review with Prisma on literature published between 2020 – 2023 with the inclusion criteria of national and international research articles in English and published in 2020-2023 relating to the title of the effect of Electronic Medical Records on Service Quality and patient satisfaction and the database source used, namely Scopus, Science Direct and PubMed. Results: Based on a comparison of hospitals that have implemented EMR vs. Paper Medical Records (PMR), it was found that implementing EMR would improve service quality more optimally than PMR. EMR enables healthcare providers to access and update patient information in real-time, quickly and accurately, increasing patient comfort and helping reduce waiting times by increasing healthcare efficiency.